Social-Psychological Factors Forming Deviant Behavior In Teenagers And Their Prevention (Eurasian Scientific Herald, 2023)
The article provides examples from studies of teachers and psychologists on the sociopsychological factors that form deviant behavior in adolescence and ways to prevent it, and in conclusion recommendations are given.